Occupational hazards, disease symptoms and physiological responses in workers with different workloads under out and indoor conditions - Ahmed, Muna; M. R, Salah; Fadlalla, IMT (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2025)
The present research work was carried during the period of January 2012 – January 2013 with the objective to assess the impact of thermal environment (indoors/outdoors) on the health workers carrying different workloads (heavy, moderate, light). The outdoor study targeted subjects working in building construction in Khartoum. The indoor study targeted subjects working in textile and glassware factories in Khartoum industrial area. The control subjects were selected from those employed at the National Health Laboratory. A questionnaire was designed to obtain information about workers pertaining to well-being, diseases complaints, and work accident etc.). Workers when asked to evaluate their workload as being heavy, moderate or light, outdoors (60%) and indoors (26%) rated their workload to the high temperature, while 30% of the control rated their works to the increase in working hours. 55% of the outdoors rated their workload to perform work rapidly. Most of the workers including the control would move their whole body while working (40 – 80%), next came moving for the outdoors (~38%), with small numbers that would stand or sit.Heat constituted most (~70%) of the hazards for indoors and outdoors workers, whereas noise and fumes were the major hazard for the control group (~20%). Nearly same percentage of outdoors workers expressed they were either exposed or not exposed to accidents while ~74% of indoor workers and 90% of the control showed that they were not exposed to accidents, with significant (P < 0.05) differences obtained between those who agreed and those did not agree. most (~88%) of the outdoor and indoor workers (~77%) did not wear protective equipment. Exposure to sunlight showed that for indoors and control there was no exposure to sunlight, however, half of the workers under outdoor conditions experienced exposure to direct sun light..Temperature sensation showed that both indoors (45%) and outdoors (47%) felt very hot, while ~35 - 40% felt hot for the indoors and control groups respectively. 60% of the control groups were not affected by the thermal environment. Excessive sweating were observed in both the control (70%) and indoor groups (72.5%). Nearly same percentages were observed for excessive (50%) and few sweating (41%) in the outdoor workers. Most (84%) of the indoor workers would respond to sweating by changing their clothes, while half of the control would do that. Outdoor workers would resolve to other solutions (37%). Most respondents of the indoors (61.5%) and half of the control expressed that they became adapted to thermal environment after employment, whereas ~44% of the outdoor respondents became adapted after days of working. Most of the indoor (97%) were not absent from their work, as with the control (70%) and out doors (55%). Absenteeism was once a week for outdoors (~20%) were absent from work once a week and 10% for the control. Reasons for being absent from work were either due to not finding work (29.4%) for outdoors or due to family issues (10%) for the control group. About half of the workers at out-and indoors almost never or somewhat felt hypersomnia, while 60% of the control felt hypersomnia and about 90% of workers at all sites felt easiness of movement.More than 60% of the workers at outdoors (67.6%), and control (70%), admitted that they suffer from some diseases, whereas most of the indoor (87.2%) did not complain from any diseases. Symptoms such as disturbed appetite (>60%) was felt by indoor and outdoor workers. Most (80 – 70%) of the workers at all sites almost never felt nausea or stomach ache diarrhea and dizziness. Same applies for symptoms as; cardiovascular disturbances,irregular heartbeats, blood rushing to the head, swollen feet and chest pain. however, 50% of the control group did complain from shortness of breath. Prevalence of the symptoms was almost felt in summer during the working day especially for outdoors (81.3%), followed by control (57.1%) and indoors (50%). For outdoor workers thirst (84.8%), sweating (51.5%), fatigue (42.4%) and rise in body temperature (39.4%) were felt during summer. For the indoor workers thirst and sweating (33%) were less important, while half of the workers felt symptoms of fatigue. For the control half of the workers felt headache, while thirst and sweating received less complaints (~33%). The prevalence of the diseases showed that depression was cited by 37% of the control. Unsteadiness, hypersomnia, insomnia, aggressiveness and lower limbs coldness were expressed by 25% of the control. Acute depression and loss of concentration was cited by 33% of indoor groups.